La calidad de la vivienda en Bogotá: Enfoque de precios hedónicos de hogares y de agregados espaciales - Morales Zurita, Leonardo; Arias Arbélaez, Fabio Alberto (Sociedad y Economía, 2005)
In this paper we estimate, for Bogotá, the social valuation of the changes in the quality attributes of the houses through the traditional hedonic price method. In addition, we estimate the effects of aggregate attributes for a zonal planning unit with adjustment in the hedonic estimation, including elements of spatial econometrics. The source of the information is: DAÑE, Encuesta de Calidad de Vida, 2003